Optimizing Strategies for Green Inventory Model with Non-Instantaneous Deterioration under Trade Credit and Sustainability Initiatives - Keswani, Mamta; Kumari, Anshu; Kumari, Komal; Khedlekar, Sudhakar; Dwivedi, Vinita (Journal of Environmental Accounting and Management, 2026)
In today's competitive business environment, organizations must collaborate to promote eco-friendly products while ensuring long-term financial sustainability. The rising demand for environmentally conscious goods has driven innovation, particularly in incorporating herbal and natural ingredients. This study introduces a green inventory model for products with non-instantaneous deterioration, designed to help organizations maximize their total annual profit under various trade credit policies. The model provides a mathematical framework to maintain sustainability through investments in environmental awareness and preservation technologies for deteriorating products, alongside trade credit strategies that support sustainable marketing efforts. The primary goal is to achieve sustainability by optimizing pricing, investing in environmental initiatives and preservation technology, and determining the optimal cycle length to maximize total profit. The model assumes that the demand rate is influenced by factors such as selling price, stock levels, and environmental awareness. From the retailer's perspective, the analysis seeks to identify sustainable ordering strategies that maximize annual profit.